Expression profiling of long non-coding RNA identifies linc-RoR as a prognostic biomarker in oral cancer. Issue 4 (March 2017) - Arunkumar, Ganesan; Deva Magendhra Rao, Arunagiri Kuha; Manikandan, Mayakannan; Arun, Kanagaraj; Vinothkumar, Vilvanathan; Revathidevi, Sundaramoorthy; Rajkumar, Kottayasamy Seenivasagam; Rajaraman, Ramamurthy; Munirajan, Arasambattu Kannan
Oral squamous cell carcinoma is the most aggressive cancer that is associated with high recurrence, metastasis, and poor treatment outcome. Dysregulation of long non-coding RNAs has been shown to promote tumor growth and metastasis in several cancers. In this study, we investigated the expression of 11 selected long non-coding RNAs that are associated with cell proliferation, metastasis, and tumor suppression in oral squamous cell carcinomas and normal tissues by quantitative real-time polymerase chain reaction. Out of the 11 long non-coding RNAs profiled, 9 were significantly overexpressed in tumors with tobacco chewing history. Moreover, the long non-coding RNA profile was similar to the head and neck cancer datasets of The Cancer Genome Atlas database. Linc-RoR, a regulator of reprogramming, implicated in tumorigenesis was found to be overexpressed in undifferentiated tumors and showed strong association with tumor recurrence and poor therapeutic response. In oral squamous cell carcinomas, for the first time, we observed linc-RoR overexpression, downregulation of miR-145-5p, and overexpression of c-Myc, Klf4, Oct4, and Sox2, suggesting the existence of linc-RoR-mediated competing endogenous RNA network in undifferentiated tumors. Taken together, this study demonstrated the association of linc-RoR overexpression in undifferentiated oral tumors and its prognostic value to predict the therapeutic response.